2022
DOI: 10.1155/2022/6750320
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Nursing Intervention Based on Risk Assessment Model on Self-Efficacy and Postoperative Rehabilitation of Surgical Patients

Abstract: The study aims to explore the effect of nursing intervention based on risk assessment model on self-efficacy and postoperative rehabilitation of surgical patients. The study applied a risk assessment model to the behavioral intervention of rehabilitation exercise in patients after percutaneous coronary intervention (PCI). A total of 157 patients were selected from a certain hospital, with 52 cases in the experimental group and 55 cases in the control group. A comprehensive cardiac rehabilitation intervention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%